Molecular characterization of environmental Cryptococcus neoformans isolated in Vitoria, ES, Brazil - Ribeiro, Mariceli Araujo; Ngamskulrungroj, Popchai (Revista do Instituto de Medicina Tropical de São Paulo, 2008)
Cryptococcus neoformans is the major cause of fungal meningitis, a potentially lethal mycosis. Bird excreta can be considered a significant environmental reservoir of this species in urban areas, thirty-three samples of pigeon excreta were collected within the city of Vitoria, Brazil. Cryptococcus neoformans was isolated and identified using standard biochemical assays in ten samples. PCR amplification with primer M13 and orotidine monophosphate pyrophosphorylase (URA5) gene-restriction fragment length polymorphism (RFLP) analysis discerned serotypes and genotypes within this species. All isolates were serotype A (C. neoformans var. grubii) and genotype VNI. The two alternative alleles a and α at the mating type locus were determined by PCR amplification and mating assays performed on V8 medium. All isolates were MAT α mating type but only 50% were able to mate in vitro with the opposite mating type MAT a tester strains (JEC20, KN99a and Bt63). This study adds information on the ecology and molecular characterization of C. neoformans in the Southeast region of Brazil.